2009
DOI: 10.1186/1471-2148-9-237
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a rapid rate of molecular evolution at the hypervariable and immunogenic Mycobacterium tuberculosis PPE38 gene region

Abstract: Background: PPE38 (Rv2352c) is a member of the large PPE gene family of Mycobacterium tuberculosis and related mycobacteria. The function of PPE proteins is unknown but evidence suggests that many are cell-surface associated and recognised by the host immune system. Previous studies targeting other PPE gene members suggest that some display high levels of polymorphism and it is thought that this might represent a means of providing antigenic variation. We have analysed the genetic variability of the PPE38 geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(132 citation statements)
references
References 73 publications
12
120
0
Order By: Relevance
“…According their calcul, Rv2108 has a volatility value of 0.1029, which place it at the 594 th rank of genes with the higher volatility among the 4099 genes values calculated. Furthermore, in agreement with the theory of an antigenic variation role, it has been observed that many PPE proteins present high levels of polymorphism like for exemple PPE38 (Rv2352c), PPE39 (Rv2353c) and PPE40 (Rv2356c) (McEvoy et al, 2009), PPE34 (Rv1917c) ), PPE42 (Rv2608) (Chakhaiyar et al, 2004), PPE8 (Rv0355c) (Srivastava et al, 2006) or PPE18 (Rv1196) (Hebert et al, 2007) and sequence variation has been observed between the orthologues of the PE and PPE protein families in in silico analyses of the sequenced genomes of M. tuberculosis H37Rv, M. tuberculosis CDC1551 and M. bovis (Gordon et al, 2001;Fleischmann et al, 2002;Garnier et al, 2003). However, this variability can not be extended to all pe/ppe family members since some are in fact conserved across strains and species (Cubillos-Ruiz et al, 2008).…”
Section: Characterization Of P27-ppe36 Proteinsupporting
confidence: 80%
“…According their calcul, Rv2108 has a volatility value of 0.1029, which place it at the 594 th rank of genes with the higher volatility among the 4099 genes values calculated. Furthermore, in agreement with the theory of an antigenic variation role, it has been observed that many PPE proteins present high levels of polymorphism like for exemple PPE38 (Rv2352c), PPE39 (Rv2353c) and PPE40 (Rv2356c) (McEvoy et al, 2009), PPE34 (Rv1917c) ), PPE42 (Rv2608) (Chakhaiyar et al, 2004), PPE8 (Rv0355c) (Srivastava et al, 2006) or PPE18 (Rv1196) (Hebert et al, 2007) and sequence variation has been observed between the orthologues of the PE and PPE protein families in in silico analyses of the sequenced genomes of M. tuberculosis H37Rv, M. tuberculosis CDC1551 and M. bovis (Gordon et al, 2001;Fleischmann et al, 2002;Garnier et al, 2003). However, this variability can not be extended to all pe/ppe family members since some are in fact conserved across strains and species (Cubillos-Ruiz et al, 2008).…”
Section: Characterization Of P27-ppe36 Proteinsupporting
confidence: 80%
“…For these interruptions to be observed they must occur in genes that are dispensable for survival of the bacterium or are redundant in function. These insertion events can also alter immune recognition or virulence properties, as has been suggested for insertions in members of the PPE gene family or in the phospholipase C gene region (McEvoy et al, 2009a, Vera-Cabrera et al, 2001. It has also been observed that the regions flanking an IS6110 insertion contain additional mutations, suggesting that this element can have a disruptive effect on the DNA region of insertion that results in mutations (Warren et al, 2000).…”
Section: Insertionsmentioning
confidence: 96%
“…This can be explained by the fact that insertions in functional genes essential for strain growth, maintenance and pathogen integrity would be harmful to the cell and thus, not maintained in the population. Preferential insertion loci or hotspots have also been identified, some of which include the phospholipase C region (Vera-Cabrera et al, 2001), members of the PPE gene family (McEvoy et al, 2009a), the dnaA -dnaN intergenic region (Turcios et al, 2009), the RD724 gene (Kim et al, 2010) and insertion into the IS1547 element (Fang et al, 1999). PPE genes are considered to be important antigens during the host-pathogen interaction and have been proposed to play a role in evasion of the immune response (Sampson, 2011).…”
Section: Insertionsmentioning
confidence: 99%
“…These preferential integration sites, are characterized by the occurrence of insertion in more than one site close each other (Sampson et al, 2001). The list of preferential sites for the insertion of this element identified at the moment rose to about half a dozen and most probably will be increased (McEvoy et al, 2009). …”
Section: Where Is6110 Can Be Insertedmentioning
confidence: 96%